Impact of Organic Matter on Iron(II)-Catalyzed Mineral Transformations in Ferrihydrite–Organic Matter Coprecipitates - ThomasArrigo, Laurel; James M. Byrne; Andreas Kappler; Ruben Kretzschmar (My University, 2018)
Poorly crystalline Fe(III) (oxyhydr)oxides like ferrihydrite are abundant in soils and sediments and are often associated with organic matter (OM) in the form of mineral-organic aggregates. Under anoxic conditions, interactions between aqueous Fe(II) and ferrihydrite lead to the formation of crystalline secondary minerals, like lepidocrocite, goethite, or magnetite. However, the extent to which Fe(II)-catalyzed mineral transformations are influenced by ferrihydrite-associated OM is not well understood. We therefore reacted ferrihydrite-PGA coprecipitates (PGA = polygalacturonic acid, C:Fe molar ratios = 0–2.5) and natural Fe-rich organic flocs (C:Fe molar ratio = 2.2) with 0.5–5.0 mM isotopically labeled 57Fe(II) at pH 7 for 5 weeks. Relying on the combination of stable Fe isotope tracers, a novel application of the PONKCS method to Rietveld fitting of X-ray diffraction (XRD) patterns, and 57Fe Mössbauer spectroscopy, we sought to follow the temporal evolution in Fe mineralogy and elucidate the fate of adsorbed 57Fe(II). At low C:Fe molar ratios (0–0.05), rapid oxidation of surface-adsorbed 57Fe(II) resulted in 57Fe-enriched crystalline minerals and nearly complete mineral transformation within days. With increasing OM content, the atom exchange between the added aqueous 57Fe(II) and Fe in the organic-rich solids still occurred; however, XRD analysis showed that crystalline mineral precipitation was strongly inhibited. For high OM-content materials (C:Fe ≥ 1.2), Mössbauer spectroscopy revealed up to 39% lepidocrocite in the final Fe(II)-reacted samples. Because lepidocrocite was not detectable by XRD, we suggest that the Mössbauer-detected lepidocrocite consisted of nanosized clusters with lepidocrocite-like local structure, similar to the lepidocrocite found in natural flocs. Collectively, our results demonstrate that the C content of ferrihydrite–OM coprecipitates strongly impacts the degree and pathways of Fe mineral transformations and iron atom exchange during reactions with aqueous Fe(II).
Keywords: Iron; Isotopes; Magnetite; Minerals; Physical and chemical processes